Students’ opinions about teaching of the controversial topics in the social studies classes - Kamil Uygun; Ibrahim Ethem Arslan (Institute of Advanced Engineering and Science, 2020)
The aim of this study is to determine middle school 7th grade students’ opinions on controversial issues. In the research, screening model and quantitative research method has been used. The sample of the study consists of 7th graders from 5 public schools located on the center of Demirci district of Manisa province. The 5-point Likert-type questionnaire prepared with 20 items has been applied to 203 students. The data has been put into the statistical program and analyzed. By determining means, deviations and frequencies of all items in the survey, it has been tabulated and interpreted separately. “Mann Whitney U” and Kruskal Wallis H” tests have been used to find out whether the students' opinions about which subjects can be discussed in the classroom, shows significant difference according to various variables or not. Interpretation of the results has been done by the significance level of 0,5. According to the findings of the research, the topics that the students want to discuss the most in the classroom respectively are human rights, multiculturalism, election system, animal rights and freedom of the press. The topics that the students do not want to discuss in the classroom are terror and violence. When the results of the research has been examined according to various variables; Significant differences has been seen in different items, such as; The Gender (Military System, Religious Communities, Fanaticism and Cloning), Reading Books (TV Broadcasts), The Education of Father (Religious Communities, Multiculturalism), The Education of Mother (Military System, Religious Communities and Cloning), Father’s Profession (Religious Communities, Fanaticism, Internet and Elections System), Mother's Profession (Religious Communities) and Family Income Status (Internet).